Ficus carica L.: metabolic and biological screening. - Oliveira, Andreia P. (2011)
Ficus carica L. is one of the earliest cultivated fruit trees. In this work, metabolite profiling was performed on the leaves, pulps and peels of two Portuguese white varieties of F. carica (Pingo de Mel and Branca Tradicional). Phenolics and organic acids profiles were determined by HPLC/DAD and HPLC/UV, respectively. All samples presented a similar phenolic profile composed by 3-O- and 5-O-caffeoylquinic acids, ferulic acid, quercetin-3-O-glucoside, quercetin-3-O-rutinoside, psoralen and bergapten. 3-O-Caffeoylquinic acid and quercetin-3-O-glucoside are described for the first time in this species. Leaves’ organic acids profile presented oxalic, citric, malic, quinic, shikimic and fumaric acids, while in pulps and peels quinic acid was absent. The antioxidant potential of the different plant parts was checked. All materials exhibited activity against DPPH and nitric oxide radicals in a concentration-dependent way. However, only the leaves presented capacity to scavenge superoxide radical. Leaves were always the most effective part, which seems to be related with phenolics compounds. Additionally, acetylcholinesterase inhibitory capacity was evaluated, but no effect was observed. Antimicrobial potential was also assessed against several bacterial species, although no activity was noticed. This is the first study comparing the chemical composition and biological potential of F. carica pulps, peels and leaves.